Concurrent Infection of Dengue and Malaria: An Unusual Case Report - Andri Baftahul Khairi; Perdana Liansyah Sihite; Rauzia Azalia (Indonesian Health Journal, 2024)
Plasmodium knowlesi is one of the most common causes of Malaria in humans. Although several reported cases of dengue and Malaria occur together, only a few cases have been reported in Southeast Asia, including Indonesia. This study aims to provide additional insight into the epidemiology and clinical aspects of Plasmodium knowlesi (P. knowlesi) malaria infection and dengue fever that occur concurrently in Southeast Asia, particularly Indonesia. A 36-year-old male patient with a history of travel to the mountainous area of Lhoknga and a fever for five days sought treatment at the emergency department of Meuraxa Hospital. During 11 days of treatment, the patient underwent a routine haematology examination every 24 hours. The average platelet count during the first eight days was around 50,000, with an increase after anti-malarial treatment on the eighth day and marked clinical improvement. The patient was discharged on day 10 with no signs of bleeding or hemolysis during treatment. Diagnosis involved blood smears and hematologic examination, confirming dengue fever with P. knowlesi malaria infection. These findings emphasize the importance of thorough history taking, physical examination, and supporting investigations to diagnose these two conditions together. The results of this study may provide critical support for case management involving malaria infection and dengue fever, with a focus on platelet monitoring as an indicator of response to treatment in the Southeast Asian region.